Enhanced Mutual Authentication System in Mobile Cloud Environments - Shanmuga Priya, S; A.Valarmathi, Dr; Rizwana, M; L.Mary Gladence, Dr (International Journal of Engineering and Technology, 2018)
Security is one of the significant worries of all associations which utilizes online methods for interchanges particularly banks. Of this, customer side is most defenseless against hacking, as the framework can't be totally shut when use over web by a typical customer is to be permitted. Most frameworks utilize a static password– based verification strategy which is anything but difficult to hack. There are different other validation strategies existing like cards, biometric recognizable proof, and so on. These strategies give better security, however are not material to online customer correspondence as these techniques require extraordinary gadgets for their usage. One conceivable technique for applying an upgraded factor of verification for online access to the framework is a dynamic secret word. In this venture we can plan the validation framework in light of key age, confirmation age and OTP based framework. The keys are created progressively utilizing Mobile IMEI number and SIM card number. The OTP age utilizes the components that are novel to the client and is introduced on a PDA in Android stage and furthermore cloud server claimed by PHP server. An OTP is legitimate for a minutes time, after which, is pointless. The framework in this way gives better customer level security – a straightforward minimal effort strategy which shields framework from hacking strategies, for example, speculating assault, answer assault, stolen and verifier assault and adjustment assault.
Keywords: Security; Password based authentication; One time Password; Mobile Cloud communication; IMEI number